Uji Efektivitas Serbuk Effervescent Ekstrak Daun Cengkeh sebagai Antijamur (Candida albicans) Penyebab Sariawan - Ilma, Amin Dyah Makrifatul; Hapsari, Fauziyyah Kunti; Mentari, Dearry; Nurul Hidayati; Ilyasa, Muhammad Rasyid Sidiq (CERATA Jurnal Ilmu Farmasi, 2024)
Clove leaves have been proven to contain compounds with pharmacological activities, such as antifungal properties. This study aims to investigate the influence of varying the amount of clove leaf extract in effervescent powder formulations as an alternative treatment for oral candidiasis. Effervescent powder was chosen as a practical and user-friendly dosage form. The variations of clove leaf extract in this study were 4%, 6%, and 8%. Effervescent powder formulations with clove leaf extract have been successfully prepared in various formulas with similar organoleptic characteristics. Physical testing, including moisture content, flow rate, pH, and dispersion, demonstrated that these effervescent powder formulas meet quality standards. Antifungal effectiveness tests revealed that Formula II has the ability to significantly inhibit the growth of Candida albicans. This suggests the potential use of clove leaf extract effervescent powder formulations in the treatment of oral candidiasis.